2021
DOI: 10.1007/s10792-021-01755-8
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of topical atropine 0.05% compared to 0.01% for myopia control in German school children: a pilot study

Abstract: Purpose Based on findings of the Asian low-concentration atropine for myopia progression study, a concentration of 0.05% has been proposed as a good compromise between safety and efficacy for myopia control. However, no data on side effects have been published so far in Caucasian children receiving this dose. Methods Prior to commencement of bilateral atropine treatment with 0.05% atropine, 19 myopic children aged 5 to 15 years were treated in only one eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
1
31
2
3
Order By: Relevance
“…The reduced visual acuities of the atropine group observed in the present study compared to the controls suggested that the enlarged pupil size after mydriasis resulted in a degradation of optical images. A loss in near vision caused by cycloplegia was found in the Asian population-based trials [23,24] and shown in the studies of Caucasian children [32,33]. The near logMAR acuity was poorer in the eyes treated with 0.05% atropine compared to the 0.01% atropine group (0.05 ± 0.06 vs. −0.01 ± 0.06 logMAR), even though a significant difference was not found due to small sample number (n = 19) [32].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The reduced visual acuities of the atropine group observed in the present study compared to the controls suggested that the enlarged pupil size after mydriasis resulted in a degradation of optical images. A loss in near vision caused by cycloplegia was found in the Asian population-based trials [23,24] and shown in the studies of Caucasian children [32,33]. The near logMAR acuity was poorer in the eyes treated with 0.05% atropine compared to the 0.01% atropine group (0.05 ± 0.06 vs. −0.01 ± 0.06 logMAR), even though a significant difference was not found due to small sample number (n = 19) [32].…”
Section: Discussionmentioning
confidence: 78%
“…A loss in near vision caused by cycloplegia was found in the Asian population-based trials [23,24] and shown in the studies of Caucasian children [32,33]. The near logMAR acuity was poorer in the eyes treated with 0.05% atropine compared to the 0.01% atropine group (0.05 ± 0.06 vs. −0.01 ± 0.06 logMAR), even though a significant difference was not found due to small sample number (n = 19) [32]. It has been demonstrated repeatedly that a combination of daily atropine treatment with distance and near correction, typically in the form of progressive addition lenses, can provide a synergistic effect on controlling the progression of myopia [34,35].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, some real-world data [35,36,40] revealed that 0.01% atropine slows the rate of myopia progression in non-Asian patients with favorable safety profiles. Joachimsen et al [44] even reported that 0.05% atropine induced significantly more anisocoria (2.9 mm compared to 0.8 mm) and loss of accommodation amplitude (loss of 4.2 D compared to 0.05 D) in Caucasian children compared to 0.01% atropine. They supposed that high variation in iris color and the affinity of atropine for melanin might be speculated for the differences [45], and this phenomenon was observed by Myles et al [40]; those with blue eyes were more susceptible to experiencing dilated pupils as a consequence of atropine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously meta-analysis revealed that patients receiving 0.01% atropine showed no significant changes in accommodative amplitude (WMD, −0.45 D; 95% CI = −1.80, 0.90; p = 0.51) over a 1-year period ( Tsai et al, 2021 ), which is consistent with our findings. However, in another study, Caucasian children receiving a concentration of 0.05 and 0.01% atropine revealed that accommodation was decreased by −4.2 ± 3.8 D in 0.05% atropine-treated eyes, whereas 0.01% atropine induced hypoaccommodation of −0.05 ± 2.5 D ( p < 0.01) ( Joachimsen et al, 2021 ). There is a nonlinear dose–response relationship between atropine and accommodative amplitude ( Tran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%